Every word you cannot say - Thomas, Iain S. (Andrews McMeel Publishing, 2019)
I know you don't want to talk sometimes. Sometimes because it hurts and sometimes because you're just not supposed to talk about what you want to talk about. Sometimes it can be hard to say, "this is beautiful," when no one else can see what you see. Or, "Here, this is where the pain is." But some part of you knows, the truth about the words you cannot say is that they only hurt until you say them. They only hurt until the person who needs to hear them, hears them. Because we are human, and the closest we've ever come to showing each other who we really are, and how we love, is with words. So I'm going to try to say to you here, what I wish you'd say to me too. Please. Listen. We can change things.